Learning Outcomes in Blended Learning Implementation - Rina Nur Hidayati; Binarti Dwi Wahyuningsih; Rudi Hariyono; Ahmad Musadek (Kirana Publisher (KNPub), 2023)
Introduction:The increasingly massive spread of the Covid 19 pandemic in the community and the existence of physical distancing rules, urged teachers to develop an effective learning model. Blended learning is the mixing of conventional (face-to-face) learning models with online learning. The purpose of this study was to determine the effectiveness of the implementation of the blended learning on the learning outcomes of community nursing practice. Method: The research design used the Pre-Experiment One Group Pretest-Post test. The sampling technique was purposive sampling, with respondents as many as 50 nursing students who met the inclusion criteria of the study. The learning outcomes research instrument used a knowledge questionnaire and practical skills observation. Data processing includes univariate analysis with percentages, and bivariate analysis using the Wilcoxon Signed Ranks Test. Results: Learning outcomes before participating in community nursing practice were 40% very good and 40% good, while the learning outcomes after participating in community nursing practice were 60% very good. There was a significant increase in learning outcomes between before and after the application of blended learning, namely being very good as much as 50%. Blended learning is proven to be effective in improving the learning outcomes (Pv 0,000, CI 95%). Conclusions: This study supports feasibility blended learning strategies based on are able to produce an increase in the learning outcomes of nursing students. The blended learning approach is an effective alternative to conventional approaches in nursing education, especially at the Ners professional stage during the Covid 19 pandemic.